2022
DOI: 10.1093/eurheartjsupp/suac022
|View full text |Cite
|
Sign up to set email alerts
|

Acute rate control in atrial fibrillation: an urgent need for the clinician

Abstract: Rate and rhythm control are still considered equivalent strategies for symptom control using the Atrial Fibrillation Better Care algorithm recommended by the recent atrial fibrillation guideline. In acute situations or critically ill patients, a personalized approach should be used for rapid rhythm or rate control. Even though electrical cardioversion is generally indicated in haemodynamically unstable patients or for rapid effective rhythm control in critically ill patients, this is not always possible due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Additionally, diltiazem has been reported to have limited efficacy in HR control. [ 5 6 ] Amiodarone should be administered with careful consideration of its side effects and risk/benefit profile. [ 7 ] While these medications are considered standard for AF HR control, it may be worthwhile to consider dexmedetomidine in certain situations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, diltiazem has been reported to have limited efficacy in HR control. [ 5 6 ] Amiodarone should be administered with careful consideration of its side effects and risk/benefit profile. [ 7 ] While these medications are considered standard for AF HR control, it may be worthwhile to consider dexmedetomidine in certain situations.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with HF who experience tachyarrhythmia, the options for acute pharmaceutical interventions are limited [ 34 ]. For hemodynamically stable patients, opting for rate control is a viable strategy until further planning is established, as in cases of AF, when ensuring the coagulation status precedes cardioversion [ 35 , 36 , 37 ]. In patients with LVEF < 40%, apart from beta-blockers, only digoxin is an alternative option for rapid rate control [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pharmacological cardioversion does not require sedation and analgesia. The selection of the mode of elective cardioversion is influenced by local practices and hospital protocols and is subject to geographic variations [1,2,59]. The RHYTHM-AF trial revealed that Sweden, Australia, United Kingdom and Germany adopted ECV as the main strategy, whereas Italy, Spain and Brazil had a strong preference for pharmacological cardioversion [60].…”
Section: Rhythm Controlmentioning
confidence: 99%
“…This is due to the fact that amiodarone has a favorable safety profile and carries a low risk of proarrhythmia. The only disadvantage is its delayed onset of action (8-24 h) [1,2,59].…”
Section: Rhythm Controlmentioning
confidence: 99%